Canadian provinces and foreign policy in Asia. (September 2018) - Labrecque, Charles-Louis; Harrison, Scott
Non-central governments in Canada have become increasingly active on the world stage, most notably in the Asia Pacific region. The scholarly works on Canada's foreign policy in Asia tend to focus either on the federal government as the main actor, or on the "other diplomacies" of non-governmental actors; little attention has been paid to the increasing role of non-central governments in Asia. This article, therefore, contributes to the discussion by documenting and evaluating Canadian provinces' international activities in the Asia Pacific. It also situates these activities within Canada's foreign policy in the region, and assesses how important provinces have become in Canada–Asia relations. This paper first reviews the literature on non-central governments and foreign policy to expose the key forces pushing and pulling Canadian provinces to be increasingly active internationally. It then details the provinces' international activities in Asia, and locates them within Canada's foreign policy in the region.